Gender Norms and Gender Equality in Full-Time Employment and Health: A 97-Country Analysis of the World Values Survey - Cislaghi, Beniamino; Bhatia, Amiya; Hallgren, Emma Sofia Thonander; Horanieh, Nour; Weber, Ann M.; Darmstadt, Gary L. (Frontiers in Psychology, 2022)
Background: Almost nowhere in the world do women participate as much as men in the labour force. Despite differences in countries’ economic, social and cultural contexts, gender norms can affect women’s labour participation across contexts. In restrictive contexts in which women are family caretakers, full time employment (FTE) might be particularly burdensome. Aims: To descriptively examine (1) the relationship between women’s access to FTE and a gender norm of equal access to labour ; (2) the relationship between FTE and men’s and women’s self-reported health (SRH) across different normative contexts; and (3) how women’s FTE and the gender norm of interest changed over time. Data: Data from the World Values Survey and European Values Survey (100 countries between 1981-2014). Sample for the cross-sectional analyses (aims 1 and 2) included 97 countries and 131,132 respondents. Sample for aim 3 included data from Argentina, Egypt, Finland and Japan. Variables: Outcome of interest was FTE-related pro-equality norms. Respondents were asked “if jobs are scarce, men should have more right to a job than women do?”. We included employment status and SRH as exposures of interest. Analysis: Descriptive, cross-sectional ecological analyses using one survey per country. We generated on-average and sex-stratified estimates of the outcome and exposures for each country. We estimated the percentage of all respondents who held pro-equality norms, the percentage in FTE, and the average level of SRH. To measure gender inequality in FTE, we also estimated the absolute difference in FTE between women and men for each country at each time point.We also examined associations between pro-equality norms and SRH. To examine if the relationship between FTE and SRH varied by normative context, we grouped countries in quartiles of pro-equality norms. Results: (1) While in some countries the gender norm of equal access to labour aligned positively with women’s access to employment, in others we found diverging results. (2) We found the association between SRH and FTE to vary across normative contexts. (3) We looked assessed the effects of economic, political and national legislative changes on FTE over time in four countries.